2017
DOI: 10.3390/ijms18030525
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Negatively Impacts Proliferation and MCTC Specific Attributes of Human Skin Derived Mast Cells, but Reinforces Allergic Stimulability

Abstract: The Vitamin-A-metabolite retinoic acid (RA) acts as a master regulator of cellular programs. Mast cells (MCs) are primary effector cells of type-I-allergic reactions. We recently uncovered that human cutaneous MCs are enriched with RA network components over other skin cells. Yet, direct experimental evidence on the significance of the RA-MC axis is limited. Here, skin-derived cultured MCs were exposed to RA for seven days and investigated by flow-cytometry (BrdU incorporation, Annexin/PI, FcεRI), microscopy, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…MC purification was achieved by positive selection with antihuman c‐Kit microbeads and the Auto‐MACS (both from Miltenyi Biotec, Bergisch Gladbach, Germany). MC purity always exceeded 98%, as assessed by acidic toluidine‐blue staining …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC purification was achieved by positive selection with antihuman c‐Kit microbeads and the Auto‐MACS (both from Miltenyi Biotec, Bergisch Gladbach, Germany). MC purity always exceeded 98%, as assessed by acidic toluidine‐blue staining …”
Section: Methodsmentioning
confidence: 99%
“…Histamine release assay (HRA) was performed according to a method routinely employed in our laboratory . In brief, MCs were stimulated by FcεRI aggregation (antiFcεRIα‐Ab 29C6 at 0.5 μg/mL), c48/80 (at 10 μg/mL), SP (at 30 μ mol/L), c48/80 + SP, or no stimulus (spontaneous) for 30 minutes at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers believe that retinoid dermatitis is an inflammatory reaction, with changes in the skin barrier being closely related to skin mast cells, probably mediated by the RA‐degrading enzyme Cyp26b1 affecting ATP receptors of mast cell . Babina et al indicated that ATRA could act on RARα in mast cells, leading to the release of cytokines such as interleukin (IL)‐1β, tumour necrosis factor‐α and IL‐8 from mast cells . However, its mechanism of action is still not fully understood, and further research on retinoid‐induced dermatitis will possibly help to avoid side‐effects in clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…4 Babina et al indicated that ATRA could act on RARα in mast cells, leading to the release of cytokines such as interleukin (IL)-1β, tumour necrosis factor-α and IL-8 from mast cells. 5,6 However, its mechanism of action is still not fully understood, and further research on retinoid-induced dermatitis will possibly help to avoid side-effects in clinical applications.…”
mentioning
confidence: 99%
“…These include downregulation of inflammatory cytokines, stimulation of alternative binding proteins, and modulation of vitamin A metabolism via synthetic as opposed to endogenous retinoids [8][9][10]. Retinoids also have an inhibitory effect on cutaneous mast cells [11]. In psoriasis, mast cells, key cellular drivers of cytokine expression and perpetuation of lesions, are found activated and in greater number in the papillary dermis [12].…”
Section: Vitamin Amentioning
confidence: 99%